2022
DOI: 10.1002/rrq.462
|View full text |Cite
|
Sign up to set email alerts
|

Turning Away from Anti‐Blackness: A Critical Review of Adolescent Reading Motivation Research

Abstract: Responding to calls for centering Black lives in our collective consciousness, this review uses Critical Race Theory to analyze researchers’ inclusion of race in conceptualizing and operationalizing adolescent reading motivation. Two questions guide this review: (1) How do researchers include race in theories of adolescent reading motivation? and (2) What assumptions do researchers make about race in studying adolescent reading motivation? What conclusions do they draw based on these assumptions? Through a sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 109 publications
0
18
0
Order By: Relevance
“…This study, which showed the instrument was not capable of capturing the girls' motivations, led me to question how adolescent reading motivation has been theorized. Critically reviewing adolescent reading motivation literature (Jones, 2022a) better enables me to design research that affirms participants. However, this criticality poses "unseen" and "unforeseen" dangers.…”
Section: Positionalitymentioning
confidence: 99%
See 4 more Smart Citations
“…This study, which showed the instrument was not capable of capturing the girls' motivations, led me to question how adolescent reading motivation has been theorized. Critically reviewing adolescent reading motivation literature (Jones, 2022a) better enables me to design research that affirms participants. However, this criticality poses "unseen" and "unforeseen" dangers.…”
Section: Positionalitymentioning
confidence: 99%
“…Reading motivation research reflects a problematic cycle: researchers have theorized reading motivation with white readers in mind, designed instruments using predominantly white samples, used those instruments empirically to compare racial groups, and drawn racialized conclusions when Black readers do not perform like their white peers (Jones, 2022a). There are a limited number of studies that specifically attend to the reading motivations of Black readers.…”
Section: Reading Motivationmentioning
confidence: 99%
See 3 more Smart Citations